"Warning Signs" of Primary Immunodeficiency among Patients with Periprosthetic Joint Infection. Issue 2 (May 2014) - Diaz-Ledezma, Claudio; Baker, Jennifer; Parvizi, Javad
Purpose: The use of ten clinical "warning signs" has been suggested as a screening tool to identify patients that may have primary immunodeficiency (PID) conditions in adulthood. This study aimed to evaluate the presence of these "warning signs" among a cohort of patients with periprosthetic joint infections (PJI), in order to detect those cases that may have had a PID contributing to development of infection. Methods: A descriptive study using our institutional PJI database was conducted. 185 patients with more than 15 medical consultations in our healthcare network before the diagnosis of PJI were considered eligible for the study. The presence of the "warning signs" was retrospectively evaluated using medical records. Results: Twenty-seven patients (14.5%) presented with one or more "warning signs" of PID; however, 24 of the individuals had another immunocompromising condition and were thought to suffer secondary immunodeficiency. Among the remaining 3 patients, PID was confirmed in 1 individual who was found to have hypogammaglobulinemia. Conclusions: It appears that some patients who develop PJI could suffer from a primary immunodeficiency status that may be detected using "warning signs" questionnaire. The administration of these questions to patients with multiple infections may lead to identification of a primary immunodeficiency status which may in turn influence the outcome of elective arthroplasty or PJI, when develops.